PENGARUH ENTREPRENEURIAL PASSION TERHADAP KEINGINAN BERWIRAUSAHA DI INDONESIA - Rizqi Anantia; Edy Yulianto Putra; Dessy Aliandrina (Jurnal Ilmiah Satyagraha, 2022)
Theory of planned behavior (TPB) consisting of personal attitude, subjective norms and perceived behaviour control are the model study about the relation of intention and behaviour. In order to expand TPB, entrepreneurial passion variabel is inserted, which is emotion effected to entrepreneur behaviour. In this research by adding predictor variabel in TPB, it is expected to enrich the explanation of entrepreneurial intention.The object of this research is entrepreneur in Indonesia. The sampling technique used is purposive sampling methode. This research uses primary data, the result of data collection using a questionnaire.  The collected data had been processed using SPSS software version 24.0. Hypothesis testing analysis uses linear regression and path analysis.The result of the research is entrepreneurial passion significantly and positevely affected entrepreneurial intention. In TPB, each construc effects entrepreneurial intention differently. Personal attitude and perceived behavioral control effect entrepreneurial intention significantly and positevely, while subjective norm affect significantly and negatively. Regarding intervening variable, personal attitude and perceived behavioral control has succesfully became intervenig variable between entrepreneurial passion and entrepreneurial intention.